Tumor necrosis factor alpha signaling in the development of experimental murine pre-hepatic portal hypertension - Theodorakis, Nicholas G (e-Century Publishing Corporation, 2010)
The cytokine tumor necrosis factor alpha (TNFa) has previously been identified in the development of portal hypertension (PHT) by facilitating portal venous and systemic hyperemia. TNFa is reported to contribute to hyperemia via endothelial nitric oxide synthase (eNOS) induction and nitric oxide (NO) production. This study examines this hypothesis by utilizing TNFa receptor knockout mice and a murine model of pre-hepatic PHT. Plasma TNFa and NOx and tissue TNFa mRNA levels were determined in wild-type mice 0-7d post induction of pre-hepatic PHT by partial portal vein ligation (PVL). TNFa receptor knockout mice also received PVL or sham surgery and splenic pulp pressure, abdominal aortic flow and portal-systemic shunting were recorded 7d following. Portal pressure and systemic hyperemia developed rapidly following PVL. Plasma NOx was increased temporarily 2-3 days following PVL and returned to baseline by day 7. Circulating TNFa was below detectable limits of the ELISA used, as such no increase was observed. Hepatic and vascular TNFa mRNA levels were transiently changed after PVL otherwise there was no significant change. TNFa receptor targeted gene deletion did not ameliorate plasma NOx following PVL and had no effect on the development of PHT. TNFa receptor signaling plays no detectable role in the development of systemic hyperemia in the murine model of pre-hepatic PHT. Consequently, increased TNFa observed in intra-hepatic inflammatory models (CCl(4)) and in patients is probably related to inflammation associated with intra-hepatic pathology. Alternatively, TNFa may be signaling via a TNFa receptor independent mechanism.